Violencia en parejas de mujeres lesbianas: Procesos de búsqueda de ayuda en Cataluña = Intimate partner violence in lesbian couples : Help-seeking processes in Catalonia - Mollá, Mónica Laliga (Oñati Socio-Legal Series, 2024)
Violence in lesbian couples is an invisible phenomenon in our society, which makes it difficult to address and intervene, especially in the processes of de-victimization. The aim of this paper is to know the help-seeking processes of lesbian women victims of this violence in Catalonia. After the implementation of a questionnaire, the results reported that many of the participants tell about the situations of violence, but not all of them decide to ask for help. Friends and psychological care stood out as the main sources of support among the participants who initiated the help-seeking process. Most of the participants sought help when situations of violence were present and the couple's relationship continued. This study, in addition to making these processes visible, points out recommendations for future research in order to continue advancing and improving the care, accompaniment and support of lesbian women victims of intimate partner violence.